2021
DOI: 10.1177/13505068211048402
|View full text |Cite
|
Sign up to set email alerts
|

She-Coronavirus: How cartoonists reflected women health workers during the COVID-19 pandemic

Abstract: Women account for 70% of healthcare workers, so their role has been – and still is – fundamental in addressing and managing the current pandemic event caused by the SARS-CoV-2 coronavirus. Far from being an opportunity to highlight the importance of women in the field, the healthcare crisis, together with lockdown policies and care responsibilities, have contributed to increase the gender gap. To study the depiction of women healthcare professionals, this paper analyses 401 cartoons on the COVID-19 pandemic th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…A study carried out by Domínguez and Sapiña (2021) collected the visual representation that nurses have had about COVID-19, highlighting how nursing is represented with a stereotyped role in which nurses (female) act as a companion to the doctor (male), as "guardian angels" dressed in miniskirts or with low necklines, etc. Our profession is still highly conditioned by sexist stereotypes that distort our image in society and undermine the importance of the profession [40].…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out by Domínguez and Sapiña (2021) collected the visual representation that nurses have had about COVID-19, highlighting how nursing is represented with a stereotyped role in which nurses (female) act as a companion to the doctor (male), as "guardian angels" dressed in miniskirts or with low necklines, etc. Our profession is still highly conditioned by sexist stereotypes that distort our image in society and undermine the importance of the profession [40].…”
Section: Discussionmentioning
confidence: 99%
“…According to the evidence, women account for 70% of healthcare workers and their role is still fundamental in the management of the COVID-19 pandemic [ 33 , 34 ]. Therefore, our finding, which showed that 66% of the participants were female, is expected.…”
Section: Discussionmentioning
confidence: 99%
“…due to protective medical clothing), and (v) non-human (e.g. when money is substituted for a patient) (see also Domínguez and Sapiña, 2022 ). The variables were tested with independent intercoder reliability tests.…”
Section: Sample and Methodsmentioning
confidence: 99%
“… González et al, 2017 ; Wood, 2011 ). For Domínguez and Sapiña (2022) , the lack of significant gender differences may be due to the underrepresentation of women cartoonists in their data (with nine cartoons, representing 2.2% of the entire sample). This has a clear echo in Anna van Heeswijk’s ‘With newspapers so male-dominated, is it any surprise that women are portrayed the way they are?…”
Section: Introductionmentioning
confidence: 99%